1998
DOI: 10.1177/089826439801000102
|View full text |Cite
|
Sign up to set email alerts
|

The Buffering Effect of a Computer Support Network on Caregiver Strain

Abstract: ComputerLink was a computer support network for family caregivers of people with Alzheimer's disease. In a 12-month experiment, 102 caregivers were randomly assigned to an experimental group that had access to ComputerLink or to a control group that did not. This investigation examined whether caregivers in the experimental group had greater reductions in four types of care-related strain by the end of the 1-year study. ComputerLink reduced certain types of strain if caregivers also had larger informal supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 35 publications
4
90
0
Order By: Relevance
“…The study by Bass et al of patients with Alzheimer disease found that computer support networks were heavily used by patients' family caregivers and significantly reduced stress among caregivers. 6 The study by Gray et al of the use of Internet and telecommunication to improve care of highrisk infants demonstrated a high Internet-use rate, with the majority initiating viewing sessions from home. 2,7 Other studies have also identified valuable success with the use of telemedicine technologies in the care of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Bass et al of patients with Alzheimer disease found that computer support networks were heavily used by patients' family caregivers and significantly reduced stress among caregivers. 6 The study by Gray et al of the use of Internet and telecommunication to improve care of highrisk infants demonstrated a high Internet-use rate, with the majority initiating viewing sessions from home. 2,7 Other studies have also identified valuable success with the use of telemedicine technologies in the care of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another experimental study, 102 Alzheimer-patient caregivers were randomly assigned to an experimental ComputerLink and control group, which revealed a "buffering effect" by the computer support on caregiver strain experienced by nonspousal caregivers with pre-existing strong support networks. 34 In another intervention study, the Comprehensive Health Enhancement Support System was used to support 51 elderly women with breast cancer seeking social support and treatment information 35 and for 204 patients with human immunodeficiency virus 36 to improve their quality of life and promote more efficient use of health care services. In these studies, the Comprehensive Health Enhancement Support System provided information, decision support, and access to experts and other patients.…”
Section: Internet Communications As Supportmentioning
confidence: 99%
“…75,76 Discussion boards have been used successfully to provide emotional and social support. [77][78][79][80] …”
Section: Limitationsmentioning
confidence: 99%